The impact of the training program and the irregular interruption in the performance of the skill and some physiological indicators of young football players - Dr. Ahmed abdul ameer hamza; Dr. Ahmed abdul ameer hamza; Dr. Tahir Yahia (الرياضة المعاصرة)
The aim of the research is to prepare a training program for young football players and to identify the effect of this training program in carrying out the skill performance and some physiological variables (heart rate, oxygen saturation, maximum consumption of oxygen, lactic acid). As well as to identify the impact of the discontinuation of the training of non-regular players in the performance of skill and some physiological indicators.